The EU's Approach to the Syrian Crisis: Turkey as a Partner? - Nas, Cigdem (ULUSLARARASI ILISKILER KONSEYI DERNEGI, 2019)
The article aims to analyze the European Union (EU)'s approach to the Syrian crisis and to evaluate the role it attributes to Turkey. The EU's approach staggered between supporting transition in Syria to a post-Assad regime and the need to protect itself against spill-over effects of the conflict. Two issues emerged as urgent priorities that determined the EU's approach to the conflict. One of them was to control the outpouring of refugees fleeing war and oppression in Syria and the other was to deal with the growing threat of terrorism, mainly the ISIL threat. The influx of Syrian refugees through the Aegean and Balkan route to the EU surged in the summer of 2015 leading to practical and political problems for EU countries. In the meantime, ISIL related terror attacks in the EU created a major security problem and led several Member States to bring back border controls in the Schengen area. The EU turned to Turkey and sought Turkey's cooperation in controlling the refugee flow and also keeping away the ISIL threat. The article looks at cooperation between Turkey and the EU and also points of contention that created hurdles in this cooperation.
Keywords: EU Foreign Policy; Turkey-EU Relations; Syrian Crisis; Refugee Crisis; International Relations